2013
DOI: 10.1194/jlr.m042754
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the HER2 pathway by n-3 polyunsaturated fatty acids prevents breast cancer in fat-1 transgenic mice

Abstract: Breast cancer (BC) remains one of the most threatening mortality factors throughout the world despite significant advancements in early detection and therapy. With a current mortality rate of 40%, over one million women worldwide will fall victim to BC. Four closely related transmembrane tyrosine kinase receptors (HER1, -2, -3, and -4) have been implicated in the pathogenesis of cancer including BC. Binding of small peptide ligand molecules to HER receptors triggers homo-or heterodimerization and autophosphory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 50 publications
(48 reference statements)
3
38
0
Order By: Relevance
“…3B), indicating that EPA inhibits Wnt/b-catenin signaling by inducing the proteasomal degradation of b-catenin. Similar results were observed in cancer cells treated with EPA and other n-3 PUFA, 22,30,31 suggesting that n-3 PUFAs have the general effect to inhibit Wnt/ b-catenin signaling in both normal and tumor cells.…”
Section: Epa Inhibits Wnt/b-catenin Signaling Through Ppard and Pparg1supporting
confidence: 72%
“…3B), indicating that EPA inhibits Wnt/b-catenin signaling by inducing the proteasomal degradation of b-catenin. Similar results were observed in cancer cells treated with EPA and other n-3 PUFA, 22,30,31 suggesting that n-3 PUFAs have the general effect to inhibit Wnt/ b-catenin signaling in both normal and tumor cells.…”
Section: Epa Inhibits Wnt/b-catenin Signaling Through Ppard and Pparg1supporting
confidence: 72%
“…These results could contribute to the mechanisms of anticancer activities of n-3 fatty acids. Furthermore, two studies using mice carrying the Fat-1 transgene, which restores the synthesis of n-3 fatty acids (EPA and DHA), inoculated with either mouse melanoma B16 cells or mouse HER2 positive breast cancer E0771 cells, showed that the development of melanoma and HER2 positive mammary gland tumors were substantially reduced after 15 days of cell inoculation while the tumors in the Fat-1 wild type (WT) mice continued to grow [79,90]. Interestingly, Xia et al demonstrated that the reduction of PGE 2 was moderate in the stromal tissues and stronger in the tumors in the Fat-1 WT mice, while PGE 3 was markedly increased in both the stromal and the tumor tissues in the Fat-1 transgenic mice with melanoma [79].…”
Section: Epa Induced Changes In 2 and 3-series Pgs In Cancermentioning
confidence: 99%
“…Interestingly, Xia et al demonstrated that the reduction of PGE 2 was moderate in the stromal tissues and stronger in the tumors in the Fat-1 WT mice, while PGE 3 was markedly increased in both the stromal and the tumor tissues in the Fat-1 transgenic mice with melanoma [79]. Similarly, there was notably increase in PGE 3 production in the mammary tumors of the Fat-1 transgenic mice compared to that in the Fat-1 WT mice [90]. The significant contribution of COX-2 to the chemopreventive activity of fish oil is further strengthened by recent findings revealing that higher consumption of n-3 PUFA (EPA and DHA) lowered the risk of aggressive prostate cancer with this effect being more pronounced in men carrying a particular COX-2 variant [14].…”
Section: Epa Induced Changes In 2 and 3-series Pgs In Cancermentioning
confidence: 99%
“…Additional mechanisms include reduced adhesion molecule expression and motility and improved insulin sensitivity [20,21]. A sum result is likely reduction in proliferation, increased apoptosis, and reduced mammary carcinogenesis [18,19,22]. …”
Section: Introductionmentioning
confidence: 99%